Oxidation of cetirizine, fexofenadine and hydrochlorothiazide during ozonation: Kinetics and formation of transformation products. (1st May 2016) - Borowska, Ewa; Bourgin, Marc; Hollender, Juliane; Kienle, Cornelia; McArdell, Christa S.; von Gunten, Urs
Abstract: The efficiency of wastewater ozonation for the abatement of three nitrogen-containing pharmaceuticals, two antihistamine drugs, cetirizine (CTR) and fexofenadine (FXF), and the diuretic drug, hydrochlorothiazide (HCTZ), was investigated. Species-specific second-order rate constants for the reactions of the molecular, protonated (CTR, FXF) or deprotonated (HCTZ) forms of these compounds with ozone were determined. All three compounds are very reactive with ozone (apparent second order rate constants at pH 7: k O3, pH7 = 1.7·10 5 M −1 s −1, 8.5·10 4 M −1 s −1 and 9.0·10 3 M −1 s −1 for CTR, HCTZ and FXF, respectively). Transformation product (TP) structures were elucidated using liquid chromatography coupled with high-resolution tandem mass spectrometry, including isotope-labeled standards. For cetirizine and hydrochlorothiazide 8 TPs each and for fexofenadine 7 TPs were identified. The main TPs of cetirizine and fexofenadine are their respective N -oxides, whereas chlorothiazide forms to almost 100% from hydrochlorothiazide. In the bacteria bioluminescence assay the toxicity was slightly increased only during the ozonation of cetirizine at very high cetirizine concentrations. The main TPs detected in bench-scale experiments were also detected in full-scale ozonation of a municipal wastewater, for >90% elimination of the parent compounds. Graphical abstract: Highlights: Reactivity of three pharmaceuticals with ozone was studied over a wide pH-range. Identification of transformation products (TPs) was performed. N -oxides were the predominant TPs of cetirizine and fexofenadine. Chlorothiazide was formed from hydrochlorothiazide. Identified TPs were found during full-scale wastewater ozonation.